Fibrotic focus: An important parameter for accurate prediction of a high level of tumor‐associated macrophage infiltration in invasive ductal carcinoma of the breast. Issue 7 (7th June 2017) - Shimada, Hiroko; Hasebe, Takahiro; Sugiyama, Michiko; Shibasaki, Satomi; Sugitani, Ikuko; Ueda, Shigeto; Gotoh, Yoshiya; Yasuda, Masanori; Arai, Eiichi; Osaki, Akihiko; Saeki, Toshiaki
Abstract : Our group and others have previously reported that a fibrotic focus is a very useful histological factor for the accurate prediction of the outcome of patients with invasive ductal carcinoma of the breast. We classified 258 cases of invasive ductal carcinoma into those with and those without a fibrotic focus to investigate whether the presence of a fibrotic focus was significantly associated with the degree of tumor‐associated macrophage (CD68, CD163 or CD204‐positive) infiltration or whether the presence of tumor‐associated macrophage infiltration heightened the malignant potential of invasive ductal carcinoma with a fibrotic focus. Multiple regression analyses demonstrated that a fibrotic focus was the only factor that was significantly associated with a high level of CD68‐, CD163‐ or CD204‐positive tumor‐associated macrophage infiltration. The combined assessment of the presence or absence of a fibrotic focus and a high or a low level of CD204‐positive tumor‐associated macrophage infiltration clearly demonstrated that CD204‐positive tumor‐associated macrophage infiltration had a significant prognostic power only for patients with invasive ductal carcinoma with a fibrotic focus in multivariate analyses; CD204‐positive tumor‐associated macrophages might only exert a significant effect on tumor progression when a fibrotic focus is present within the invasive ductal carcinoma of the breast.